2022
DOI: 10.1155/2022/7518533
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thrombocyte Parameters in Retinopathy of Prematurity Development

Abstract: Purpose. To investigate the role of thrombocyte parameters in retinopathy of prematurity (ROP) development. Materials and Methods. This retrospective study included 120 preterm infants in total. Group 1 was formed by infants who developed type-1 ROP and received treatment. Group 2 was formed by infants who developed ROP and were not treated for ROP. Infants who did not develop ROP and whose retinal vascularization was completed in their follow-up formed Group 3. Gestational age, birth weight, and genders of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The study included 120 preterm infants segregated into three groups: Group 1- infants who developed type-1 ROP and received treatment; Group 2- infants who developed ROP and were not treated for ROP; and Group 3- infants who did not develop ROP. The results did not show a statistically significant difference between the evaluated groups regarding the evaluated thrombocyte parameters [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included 120 preterm infants segregated into three groups: Group 1- infants who developed type-1 ROP and received treatment; Group 2- infants who developed ROP and were not treated for ROP; and Group 3- infants who did not develop ROP. The results did not show a statistically significant difference between the evaluated groups regarding the evaluated thrombocyte parameters [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers, such as metabolites, cytokines, growth factors, non-coding RNAs, gut microbiota, or oxidative stress markers, have been proposed for the diagnosis or prediction of ROP [ 13 ]. The role of thrombocyte parameters in the prediction of ROP has been studied in several papers that have outlined the involvement of these elements in neoangiogenesis [ 14 ]. Thrombocytopenia, mean platelet volume (MPV), and platelet mass index (PMI) have been proven to be promising biomarkers for the prediction of ROP in various studies [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in PLT count results in reduced VEGF elimination, leading to an increase in VEGF and subsequent massive neovascularization. Most studies ( 21 , 23 , 26 ) have found an association between thrombocytopenia and development or severity of ROP; however, a few studies ( 7 , 27 ) detected no association between low PLT levels and ROP. Choręziak et al ( 27 ) found no difference in the early postnatal PLT count between patients with ROP that do and do not require treatment.…”
Section: Effect Of Hematological Indicators On Ropmentioning
confidence: 99%
“…In recent years, an increasing number of studies ( 7-11 ) have revealed that various laboratory markers in children, including hemoglobin (Hb), platelet count, blood glucose (BG) and inflammatory cells, may be linked to the development of ROP ( Table I ). These findings demonstrate the etiology of ROP and its association with systemic reactions.…”
Section: Effect Of Hematological Indicators On Ropmentioning
confidence: 99%
See 1 more Smart Citation